Budaya Belajar Sejarah Siswa Kelas XI MIPA SMA Swasta Mulia Pratama - Lucy Octania Sianturi; Anisa Permata Sari; Putri Christina Br Tarigan; Najuah Najuah Najuah (BEST Journal (Biology Education, Sains and Technology), 2022)
In the same view, the culture of learning is understood as a habit that the individual applies to perform his learning tasks. The learning culture embraced by extraordinarily intelligent students cannot be separated from the learning environment that has shaped it, namely the school. The school has a strong organizational culture and is based on certain values and norms that affect the learning culture of students. History is a dialogue between past events and future developments. Understanding history needs to be owned by everyone from an early age in order to know and understand the meaning of past events. This research uses qualitative descriptive research methods with a research location at THE Mulia Pratama Private High School. History learning activities for class XI students of Sma Swasta Mulia. Literacy / reading training conducted by teachers follows the principles of teaching optimal performance literacy. Both in understanding and applying the material received by them.